2023
DOI: 10.1111/srt.13354
|View full text |Cite
|
Sign up to set email alerts
|

A novel optical coherence tomography‐based in vitro method of anti‐aging skin analysis using 3D skin wrinkle mimics

Abstract: Background Wrinkles represent a characteristic symptom of skin aging. In recent years, various studies have focused on their prevention and/or cure. However, clinical tests are still the only method available to directly detect and evaluate the anti‐wrinkle efficacy of various substances. Moreover, no in vitro strategy for such anti‐aging skin analysis has been reported. Therefore, in this study, we aimed to develop a novel technology to overcome these limitations. Materials and methods Full‐thickness (FT) ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“… 27 For wrinkle evaluation, methods that indirectly measure the depth of wrinkles by manufacturing a replica at the 2D level, or those that measure the actual skin depth at the 3D level using fringe projection, are used. 28 , 29 , 30 However, other than these methods, it is difficult to accurately evaluate the dermis without using biopsy. Non‐invasive tape stripping has emerged as an alternative method for evaluation because biopsy is invasive and can cause scars; however, it has been reported that the tape stripping method is ineffective in reflecting changes in the dermis, the skin layer in which most molecular biological reactions of skin aging occur, because the collection area of the sample is limited to the epidermis.…”
Section: Discussionmentioning
confidence: 99%
“… 27 For wrinkle evaluation, methods that indirectly measure the depth of wrinkles by manufacturing a replica at the 2D level, or those that measure the actual skin depth at the 3D level using fringe projection, are used. 28 , 29 , 30 However, other than these methods, it is difficult to accurately evaluate the dermis without using biopsy. Non‐invasive tape stripping has emerged as an alternative method for evaluation because biopsy is invasive and can cause scars; however, it has been reported that the tape stripping method is ineffective in reflecting changes in the dermis, the skin layer in which most molecular biological reactions of skin aging occur, because the collection area of the sample is limited to the epidermis.…”
Section: Discussionmentioning
confidence: 99%